The effect of microstructure on corrosion behavior of a novel AlCrTiSiN ceramic coating. Issue 8 (1st June 2020) - Chen, Wanglin; Hu, Te; Wang, Chengyong; Xiao, Hui; Meng, Xianna
Abstract: A novel AlCrTiSiN ceramic coating was deposited on 316L austenitic stainless steel (ASS) to enhance its anti-corrosion against 10 vol% HCl solution. Meanwhile, an AlCrN coating was selected for comparison. The results show the AlCrTiSiN consists entirely of single-phase fcc-AlCrTiSiN solid solution, showing nano-multilayered structure. While the AlCrN coating is composed of single-phase fcc-AlCrN solid solution, revealing a typical columnar structure. Growth-related micro-particles (MPs) induce the transformation of growth behavior of the AlCrTiSiN coating over MPs from nano-layered structure to columnar structure, resulting in a reduction in coating densification. Corrosion mechanisms of AlCrTiSiN-coated sample are: pitting corrosion first arrives from surface defects and columnar GBs, and then propagate towards coating subsurface until steel substrate, leading to local corrosion. Subsequently, the galvanic corrosion between coating and substrate happens, resulting in the rapid dissolution of steel substrate beneath the coatings. The combination of pitting corrosion, local corrosion and galvanic corrosion further induces the corrosion cracking, and finally results in coating delamination. In addition, layered interfaces induce the deflection of corrosion cracks along layered interfaces, and further retard the dissolution of coating. Electrochemical and immersion tests confirm that the AlCrTiSiN-coated sample shows a superior corrosion resistance compared with AlCrN-coated one. Superior anti-corrosion of AlCrTiSiN ceramic coating is mainly related to its lower MP number density, denser structure and high-density layered interfaces parallel to coating surface.